AH-19 The Heavy Metal Deposit Visualization on Organ Tissues after Slaughtering on Beef Production - Adi Winarto; I Ketut Mudite Adnyane; Yohana Paula Prihatmi Pamungkasari (Media Veteriner, 2015)
The Heavy Metal Deposit Visualization on Organ Tissues after Slaughtering on Beef Production